An Inverse Correlation of Serum Fibroblast Growth Factor 19 with Abdominal Pain and Inflammatory Markers in Patients with Ulcerative Colitis - Magdalena Panek-Jeziorna; Agata Mulak (Gastroenterology Research and Practice)
Background and Aims. Bile acids (BA) play an important role in the modulation of numerous gut functions. Fibroblast growth factor 19 (FGF19) is the ileal hormone regulating BA homeostasis. The aim of the study was to evaluate serum FGF19 level and its correlation with clinical and endoscopic disease activity indices along with inflammatory biomarkers including serum CRP and fecal calprotectin levels in patients with ulcerative colitis (UC). Methods. Fasting serum FGF19 level was measured using ELISA test in 16 patients with active UC (7 F, 9 M), 15 patients with nonactive UC (8 F, 7 M), and 19 healthy controls (11 F, 8 M). The disease activity was assessed based on the clinical and endoscopic evaluations as well as serum CRP and fecal calprotectin level measurement. Results. The median serum FGF19 level was higher in patients with nonactive UC (175.3 pg/ml (108.7-342.3)) than in patients with active UC (114.3 pg/ml (68.9-155.3), p=0.093). The median FGF19 level in healthy controls amounted to 151.6 pg/ml (90.6-224.2), and there were no statistically significant differences between the patients with active and nonactive UC compared to the healthy controls. An inverse correlation was observed between FGF19 level and abdominal pain intensity (R=–0.48, p=0.007) as well as fecal calprotectin (R=–0.38, p=0.036) and CRP levels (R=–0.36, p=0.045). The serum FGF19 level was not correlated neither with clinical nor endoscopic disease activity indices. Conclusions. The inverse correlations between FGF19 level and abdominal pain as well as inflammatory markers in UC may imply its potential analgesic and anti-inflammatory effects.